2022
DOI: 10.1093/bjc/azac063
|View full text |Cite
|
Sign up to set email alerts
|

Pathways to Drug Dealing in the Middle and Upper Classes: Early Marginalization, Relative Disadvantage and Countercultural Opposition

Abstract: Drug dealing is widespread in all sectors of society but is still studied predominantly in disadvantaged urban areas. We identify three main pathways to drug dealing based on qualitative interviews with middle- and upper-class individuals in Oslo, Norway. First, problems in the family and school and a lack of belonging in affluent neighbourhoods intersected with drug use and eventually led to recruitment into the illegal drug economy. Second, criminal entrepreneurship developed among relatively disadvantaged p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Before the introduction of various online markets, these types of sellers operated in more separate parts of the market. Recreational sellers relate to social supply (i.e., dealings with friends), whereas sellers with commercial engagement in terms of volume have an open network of buyers (e.g., Berger et al, 2022;Jacques & Wright, 2015;May & Hough, 2004). We may speculate that because social media markets do not call upon the same level of digital capital as in darknet markets, we may see an even higher degree of mixing between recreational and commercial sellers in social media markets (Bakken et al, 2023).…”
Section: State Of the Artmentioning
confidence: 99%
“…Before the introduction of various online markets, these types of sellers operated in more separate parts of the market. Recreational sellers relate to social supply (i.e., dealings with friends), whereas sellers with commercial engagement in terms of volume have an open network of buyers (e.g., Berger et al, 2022;Jacques & Wright, 2015;May & Hough, 2004). We may speculate that because social media markets do not call upon the same level of digital capital as in darknet markets, we may see an even higher degree of mixing between recreational and commercial sellers in social media markets (Bakken et al, 2023).…”
Section: State Of the Artmentioning
confidence: 99%
“…And Jacinto et al (2008) argued that transitions into drug sales can also be driven by (9) profit motives, and more conscious choices. Finally, a recent study by Berger et al (2022) found that (10) ideological idealism, aimed at promoting a drug liberalisation agenda, can also play a role in middle-class individuals' drift into drug sales.…”
Section: Analytical Framework: Drifting Into and Out Of Drug Salesmentioning
confidence: 99%
“…Moeller, 2017;Søgaard et al, 2019;Kalkan, 2021). As noted by Salinas (2018), however, there is today a small but growing body of research that explores drug sales among society's more privileged groups (see Curcione, 1997;Mohamed & Fritsvold, 2010;Jacques & Wright, 2015;Salinas, 2018;Perrin et al, 2021;Berger et al, 2022). Furthermore, recent years have also seen a growth in studies focusing on so-called 'friendship markets' (Dickinson, 2017), composed of relatively mainstream young people who, aside from using drugs and functioning as 'friend suppliers' , live largely law-abiding lives (Coomber & Turnbull, 2007;Duffy et al, 2008;Potter, 2009;Coomber, 2010).…”
Section: Introductionmentioning
confidence: 99%